2016
DOI: 10.1038/srep35072
|View full text |Cite
|
Sign up to set email alerts
|

A long-acting GH receptor antagonist through fusion to GH binding protein

Abstract: Acromegaly is a human disease of growth hormone (GH) excess with considerable morbidity and increased mortality. Somatostatin analogues are first line medical treatment but the disease remains uncontrolled in up to 40% of patients. GH receptor (GHR) antagonist therapy is more effective but requires frequent high-dose injections. We have developed an alternative technology for generating a long acting potent GHR antagonist through translational fusion of a mutated GH linked to GH binding protein and tested thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
4
0
5
Order By: Relevance
“…More recently Wilkinson et al demonstrated that fusion of GHBP to a GHR antagonist protein similar to B2036 significantly reduced IGF1 by 14% after a single subcutaneous injection in rabbits and may be useful for treating acromegaly. 128 Introduction of a W104A mutation in the fused GHBP prevented intra- and inter-molecular binding. Three chimeric GHR antagonists were generated with extended in vivo clearance times; the terminal half-life of the fusion proteins was greater than 20 h in rats.…”
Section: Strategies That Target Ghr Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently Wilkinson et al demonstrated that fusion of GHBP to a GHR antagonist protein similar to B2036 significantly reduced IGF1 by 14% after a single subcutaneous injection in rabbits and may be useful for treating acromegaly. 128 Introduction of a W104A mutation in the fused GHBP prevented intra- and inter-molecular binding. Three chimeric GHR antagonists were generated with extended in vivo clearance times; the terminal half-life of the fusion proteins was greater than 20 h in rats.…”
Section: Strategies That Target Ghr Signalingmentioning
confidence: 99%
“…Three chimeric GHR antagonists were generated with extended in vivo clearance times; the terminal half-life of the fusion proteins was greater than 20 h in rats. 128…”
Section: Strategies That Target Ghr Signalingmentioning
confidence: 99%
“…La GH posee una estructura tridimensional que comprende cuatro hélices alfa, empaquetadas estrechamente con cadenas adyacentes no helicoidales en un haz antiparalelo que contiene dos puentes de disulfuro (18,20). Las hélices antiparalelas se conectan en un patrón de "arriba-arriba-abajo-abajo" con el núcleo del haz de cuatro hélices que contribuye a estabilizar la estructura y a mantener la configuración empaquetada (21), posee dos dominios de unión al receptor separados: el sitio 1 y el sitio 2 (22), donde el sitio 1 es de alta afinidad mientras que el 2 es más débil (23).…”
Section: Hormona De Crecimiento (Gh)unclassified
“…Fuente: elaboración propia. (20,23) y se compone de aproximadamente 620 aminoácidos (19), este se encuentra en diferentes tejidos como hígado, tejido adiposo, músculo, próstata, riñón, placenta, corazón, cerebro y glándula mamaria (21,27).…”
Section: Ghr E Interacción Gh-ghrunclassified
See 1 more Smart Citation